Piano Teachers’ Job Satisfaction in Music Schools in the Republic of Croatia - Sabljar, Mirna; Opić, Siniša; Šulentić Begić, Jasna (Revija za elementarno izobraževanje, 2020)
This is the first major research targeting a specific group of teachers, shaped with the idea of gathering empirical indicators of piano teachers’ job satisfaction. More than half of music schools’ piano teachersparticipated (N=253) from all the counties of the Republic of Croatia. The results have shown that piano teachers are moderately satisfied, that there are no differences when it comes to gender, nor with the type of school where they teach. Teachers with more years of experience are more satisfied with their work, similar to teachers who have advanced in their professional area. The results can contribute to improving teaching practice and effectiveness, with the further outcome being pupils achieving higher educational attainments.
Keywords: piano teaching, one-toone teaching, music schools, piano teachers, job satisfaction